Neonatal Screening for SCID: The French Experience - Marie Audrain; Caroline Thomas (MDPI AG, 2021)
After it was demonstrated in 2005 that T cell receptor excision circle (TREC) quantification for dried blood spot (DBS) samples on Guthrie cards is an effective means of SCID screening and following several pilot studies, the practice was formally recommended in the US in 2010. More and more countries have adopted it since then. In France, before the health authorities could recommend adding SCID to the list of five diseases that were routinely screened for, feasibility and cost-effectiveness studies had to be conducted with a sufficiently large cohort of neonates. We carried out three such studies: The first sought to verify the effectiveness of the assay. The second, DEPISTREC, evaluated the feasibility of universal SCID screening in France and assessed the clinical benefit and economic advantage it would provide. Through the third study, NeoSKID, still under way and to continue until recommendations are issued, we have been offering SCID screening in the Pays de la Loire region of France. This review briefly describes routine newborn screening (NBS) and management of primary immunodeficiency diseases (PIDs) in France, and then considers the lessons from our studies and the status of SCID screening implementation within the country.